Neuroticism and Social Media Addiction - Muhammad Afif Alhad (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
The rise in levels of social media users among millenials and post millenials raises the question of what makes individuals spend much time on social media. Individuals use social media platforms for various kinds of activities. The current study examined the link between neuroticism personality trait and social media addiction. This study used quantitative approach to find out how neuroticism relate to social media addiction using linear regression analysis. Results indicated that neuroticism had significant positif role toward social media addiction. Furthermore neuroticism explained 4.8% variance of social media addiction.